Incidence and Clinical Outcomes of Streptococcus anginosus in Acute Complicated Sinusitis: A Pediatric Cohort. (11th January 2020) - Troy, Elizabeth; Sillau, Stefan; Bernard, Timothy J; Rao, Suchitra
Abstract: We conducted a retrospective cohort study of 160 hospitalized children admitted for acute complicated sinusitis and compared children with S anginosus– associated infection to children with other or no pathogens identified. The incidence of S anginosus –associated infections increased 12% per year, and infections with S anginosus are associated with increased morbidity.